The recall of elected officeholders the growing incidence of a venerable, but overlooked, democratic institution. Issue 8 (17th November 2018) - Whitehead, Laurence
ABSTRACT: Scattered case studies of recall procedures can be found in the literature on particular countries, and recent literature has drawn attention to the growth and diffusion of this family of practices. But the long genealogy, and the wide international distribution, of the recall process has been overlooked in the broader study of democratization, institutional design, and political representation. This article presents the two original country studies and situates them within the emerging field of comparative research. Four major themes are highlighted: the multiple and often subterranean sources of these experiments; their fluctuating profiles and (mostly) low external visibility; the relative weight of diffusion versus independent invention; and the resulting design pitfalls, as well as the potential benefits when carefully introduced.